BOBBY SAPUTRA AND HIS SATIRE IN THE DIGITAL REALM: A VISUAL-VERBAL VIDEO ANALYSIS - Rahmawati, Chatarina Tri (University of Muhammadiyah Malang, 2024)
Satire is a linguistic device that can be used as a way to ridicule or critique certain people or group of community. There had been numerous studies related of the use of satire in the world of politics, yet almost none of them addressed the nonpolitical aspect. The use of satire extends beyond political news, rather it has been starting to appear on certain social media posts on social media, including platforms like TikTok. This study sought on the way satire was utilized in some TikTok videos made by @supercoolben10 that were mostly talking about the life of upper class society. To add the novelty of this qualitative study, VVVA (Visual-Verbal Video Analysis) framework was utilized in analyzing the video. After a number of seven videos underwent the six processes of VVVA, it was found that both visual and verbal components take parts in constructing a good satire that could be used as a social critique. The findings in this study were presented into four sub-topics: 1) Satire as Social Critique on Economic Inequality, 2) The Role of Visual and Verbal Elements in Satire, 3) Effectiveness of VVVA for Analyzing Satire on TikTok, and 4) Broader Implications for Satire and Social Critique on Digital Platforms.